GREEN BUILDING INDEX MALAYSIA: DRIVERS AND BARRIERS OF IMPLEMENTING IT IN THE MALAYSIAN CONSTRUCTION INDUSTRY - SALEHUDDIN, MUHAMMAD YAZID (2010)
Green building or sustainable building is defined in different ways but they share common view that it should be design and operated to reduce negative impact on environment and human health. These design include how efficient the energy, water and other resources been consumed. Another factor it consider is how the management of the waste and pollution is been conducted throughout the construction process. In recognition of these problems, a number of tools have been developed to evaluate the performance of the building in terms of the impact on environment. Malaysia also has developed their green rating tools called Green Building Index (GBI). It was launched on April 2009 and developed by Pertubuhan Arkitek Malaysia (PAM) and the Association of Consulting Engineers Malaysia (ACEM). This research will go deeply on the characteristic of GBI compared to other green rating tools worldwide specifically in residential properties. The research will follow by a survey distributed to professional who involved the building construction industry to obtain their opinion on GBI. The survey will help gather some information on the respondent's (professional) opinion, knowledge and perception of the implication of GBI in Malaysia. After the survey is finished, the researcher will list out the drivers and barriers in implementing the GBI in Malaysia and discuss the solution for it.